PENGARUH VARIASI TEMPERATUR TERHADAP MASSA DAN ENERGI YANG DIHASILKAN PIROLISIS SERBUK KAYU MAHONI (SWITENIA MACROPHYLLA) PADA ROTARY KILN - Qiram, Ikhwanul; Widhiyanuriyawan, Denny; wijayanti, widya (ROTOR, 2015)
Pirolysis is thermochemical decomposition process of biomass into useful product. A method that can be used is a rotary kiln pirolyzer which consist a heating cylinder that rotate with a certain rotation speed. This research is aimed to get the effet of temperature due to char product quantity of switenia macrophylla rotary kiln pirolysis.The research is done by pirolysis experiment with 200 gram of switenia macrophylla in dust form. Temperature heating is varied 250 C, 350 C, 450 C, 500 C, dan 600 C. The heating temperature is provide by eletric heater with control system. Temperatur is measured with K type thermocouple. The heating process is taken for 180 minutes using stopwatch. The measurement is done for biomass and char volume using measuring cup. Mass is measured using scale. Low heating value is measured using bomb calorimeter.The result show that temperatur has effect due to char product of switenia macrophylla rotary kiln pirolysis. Char mass loss tend to increase due to temperature increasing. Low heating value and char porosity tend to increase due to mass loss percentage increasing. Shrinking factor and percentage of yield energy tend to decrease due to mass loss percentage increasing. Keywords: pirolysis, rotary kiln, char, temperature